Gacha Addiction and In-App Purchases: a Study on Genshin Impact Players in Indonesia - Cokki Cokki; Haris Maupa; Wanstum Wanstum; Syarifuddin Sulaiman (MATRIK: JURNAL MANAJEMEN, STRATEGI BISNIS, DAN KEWIRAUSAHAAN, 2025)
The purpose of this study was to examine the impact of gacha addiction and good price on the intention topurchase in-app items, with mobile game loyalty as a mediating variable. The research employed a quantitativeapproach using Partial Least Squares-Structural Equation Modeling (PLS-SEM) to analyze survey datacollected from 208 Genshin Impact players in Indonesia through random sampling and online questionnaires.The results indicate that gacha addiction significantly influences the intention to purchase in-app items, whilegood price has a moderate effect. Additionally, mobile game loyalty serves as a partial mediator in therelationship between gacha addiction and purchase intention.